# cos(3x)cos(x)=sin(3x)sin(x)

## Simple and best practice solution for cos(3x)cos(x)=sin(3x)sin(x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for cos(3x)cos(x)=sin(3x)sin(x) equation:

Simplifying
cos(3x) * cos(x) = sin(3x) * sin(x)
Remove parenthesis around (3x)
cos * 3x * cos(x) = sin(3x) * sin(x)
Reorder the terms for easier multiplication:
3cos * x * cos * x = sin(3x) * sin(x)
Multiply cos * x
3cosx * cos * x = sin(3x) * sin(x)
Multiply cosx * cos
3c2o2s2x * x = sin(3x) * sin(x)
Multiply c2o2s2x * x
3c2o2s2x2 = sin(3x) * sin(x)
Remove parenthesis around (3x)
3c2o2s2x2 = ins * 3x * sin(x)
Reorder the terms for easier multiplication:
3c2o2s2x2 = 3ins * x * ins * x
Multiply ins * x
3c2o2s2x2 = 3insx * ins * x
Multiply insx * ins
3c2o2s2x2 = 3i2n2s2x * x
Multiply i2n2s2x * x
3c2o2s2x2 = 3i2n2s2x2
Solving
3c2o2s2x2 = 3i2n2s2x2
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Divide each side by '3o2s2x2'.
c2 = i2n2o-2
Simplifying
c2 = i2n2o-2
Take the square root of each side:
c = {-1ino-1, ino-1}`